2015
DOI: 10.1111/jels.12090
|View full text |Cite
|
Sign up to set email alerts
|

Does Juvenile Delinquency Reduce Educational Attainment?

Abstract: This article investigates the effect of delinquency in youth on subsequent educational attainment. To do so, we focus on delinquent acts committed by age 16 and examine their impact on two measures of educational attainment: high school graduation and college graduation. Using information on males from the extremely rich National Longitudinal Survey of Youth 1997, we find plausible evidence that delinquency by age 16 reduces the likelihood of graduating from high school and college. This effect is driven by ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 76 publications
0
7
0
1
Order By: Relevance
“…Antisocial behavior involves the repeated violation of social norms in various contexts, which can entail physical or emotional hostility towards others, disrespect for authority and unlawful conduct (Bartol & Bartol, 2015;Maruschi, Estevão, & Bazon, 2014;Murray, Cerqueira, & Kahn, 2013;Souza & Resende, 2016;Ward & Williams, 2014). Brazilian legislation holds juveniles responsible for delinquency by way of socioeducational (correctional) measures in Juvenile Court (Law no.…”
Section: Evaluación De Un Programa De Desarrollo De Habilidades Académentioning
confidence: 99%
“…Antisocial behavior involves the repeated violation of social norms in various contexts, which can entail physical or emotional hostility towards others, disrespect for authority and unlawful conduct (Bartol & Bartol, 2015;Maruschi, Estevão, & Bazon, 2014;Murray, Cerqueira, & Kahn, 2013;Souza & Resende, 2016;Ward & Williams, 2014). Brazilian legislation holds juveniles responsible for delinquency by way of socioeducational (correctional) measures in Juvenile Court (Law no.…”
Section: Evaluación De Un Programa De Desarrollo De Habilidades Académentioning
confidence: 99%
“…The author further suggests that the mechanism of this effect can be explained by the impact of stigma's that arise from interactions with juvenile justice. Ward and Williams (2014) study the relationship between self-reported delinquency and educational outcomes. They find that delinquency by age 16 appears to reduce the likelihood of graduating from high school by up to 10…”
Section: The Effects Of Criminal Behavior On Educational Outcomesmentioning
confidence: 99%
“…We also perform similar approach and let  vary between 0 and 0.25 (with 0.05 intervals) for primary education and let  vary from 0 to -0.25 (with 0.05 intervals) for higher education. The range of  commonly used in the literature varies from 0 to 0.5 or to -0.5 (Altonji et al, 2005;Hjalmarsson, 2008;Ward and Williams, 2014). The negative  -values for higher education indicate that the correlation between criminal involvement of parents and higher education is negative.…”
Section: The Relationship Between Criminal Involvement Of Parents and Educational Attainment Of Their Childrenmentioning
confidence: 99%
See 2 more Smart Citations